Comments on regularization ambiguities and local gauge symmetries - Casana, R.; Pimentel, B. M. (World Scientific Publ Co Pte Ltd, 2005)
We study the regularization ambiguities in an exact renormalized (1 + 1)-dimensional field theory. We show a relation between the regularization ambiguities and the coupling parameters of the theory as well as their role in the implementation of a local gauge symmetry at quantum level.
Keywords: theory of quantized fields; gauge field theories; symmetry and conservation laws